2017
DOI: 10.1186/s40645-017-0134-9
|View full text |Cite
|
Sign up to set email alerts
|

Possible climate preconditioning on submarine landslides along a convergent margin, Nankai Trough (NE Pacific)

Abstract: Submarine landslides are major agents of sediment mass transfer from the shallow to deep sea. Due to their rapid emplacement and tsunamigenic potential, such landslides are significant geohazards for society and offand on-shore infrastructure. The relationship between climate change and the occurrence of submarine landslides is widely debated. However, there is a lack of continuous long-term submarine landslide records with which to comprehensively understand the relationship between climate-driven forces and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Expeditions 316, 333 and 338 (Expedition 316 Scientists, 2009a, 2009bExpedition 333 Scientists, 2012;Moore et al, 2014) and postexpedition stable isotope and tephra-stratigraphy (Kremer et al, 2017). Continuous horizons were restored to subhorizontal by back slipping along faults, while restoration of beds truncated or offset by erosion (e.g., slope failure) were restored manually via geometric interpolation between the eroded and onlap surfaces (e.g., Horizons O and M between Figures S3 and S4 in the supporting information).…”
Section: 1029/2020gc009038mentioning
confidence: 99%
See 2 more Smart Citations
“…Expeditions 316, 333 and 338 (Expedition 316 Scientists, 2009a, 2009bExpedition 333 Scientists, 2012;Moore et al, 2014) and postexpedition stable isotope and tephra-stratigraphy (Kremer et al, 2017). Continuous horizons were restored to subhorizontal by back slipping along faults, while restoration of beds truncated or offset by erosion (e.g., slope failure) were restored manually via geometric interpolation between the eroded and onlap surfaces (e.g., Horizons O and M between Figures S3 and S4 in the supporting information).…”
Section: 1029/2020gc009038mentioning
confidence: 99%
“…and C0022 (Expedition 316 Scientists, 2009a, 2009bExpedition 333 Scientists, 2012;Moore et al, 2014), and oxygen isotope and tephra-stratigraphy at C0018 help constrain the age of Horizon O to 0.9 Ma (Kremer et al, 2017). Here, we chose to use an average date for each horizon, as determined by the different dating methods, to provide a single target date for our restorations.…”
Section: 1029/2020gc009038mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as noted by Moore and Strasser (2016), the recurrence interval for landsliding in the Kumano Basin appears to be about 0.05 to 0.1 Ma, which is much less frequent than the recurrence interval for Nankai's great earthquakes. Kremer et al (2017) suggested that this difference could be due to slopes being preconditioned to fail because of climate forcing during interglacial periods. However, they were unable to resolve the relative contributions of tectonic versus climate preconditioning factors, and Urlaub et al (2013) showed that the ages of landslides on passive margins can be described by a temporally random Poisson distribution and therefore do not show a positive correlation between the frequency of major slope failures on passive margins and sea level changes during the past 0.18 Ma.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies rely on a reconstruction of events based on marine geophysical and geological records. For example, multibeam bathymetry data are now routinely used to characterize the morphological expression of failures and associated deposits (e.g., Hill et al, 2020; Watson et al, 2020), seismic reflection data are used to map the substrate architecture of failure zones (e.g., Berndt et al, 2012; Brothers et al, 2018), and measurements from seafloor drilling/coring provide constraints on geotechnical parameters and the age of sedimentary units involved in the failure process (e.g., Ikari et al, 2011; Kremer et al, 2017). Studies focused on incipient failure or on preconditioning factors have been conducted along many margins around the world (e.g., Bryn et al, 2005; Kvalstad et al, 2005; Piedade et al, 2018; Song et al, 2020), including regions undergoing compressional tectonics and uplift (e.g., Alves et al, 2014; Gee et al, 2007; Gross et al, 2018; Ikari et al, 2011); however, such studies are limited along the U.S. West Coast.…”
Section: Introductionmentioning
confidence: 99%